STUDENTS’ STRATEGIES IN LEARNING ENGLISH VOCABULARY AT YAYASAN ISLAMIC CENTRE SUMATERA UTARA - Putri Mulya Suci Lubis and Rafika Dewi Nasution (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
This study deals with the students‟ strategies in learning English vocabulary at Yayasan Islamic Centre Sumatera Utara. The objectives of the study were to investigate strategies of students in learning English vocabulary and elaborate the students‟ reasons for those strategies in learning English vocabulary.This study was conducted by using descriptive qualitative method. The data in this study were students‟ responses that gained through questionnaires and transcript of recorded interview of the students of the eighth grade at Islamic Centre Sumatera Utara.The instruments for collecting data were observation, questionnaire and interview. The data were analyzed based on theory by Cook (2008). The findings indicated that there are six strategies from two categories are used by the subjects in learning English vocabulary. Namely, category 1: Strategies for getting meaning: (1) guessing from situation or context, (2) using a dictionary, (3) make deductions from the word form and category 2: Strategies for acquiring words: (4) repetition and rote learning, (5) organizing words in the mind, (6) linking to existing knowledge. It is also found that using a dictionary is the dominant strategy used by the subjects. It is caused by the subjects‟ limitation in vocabulary. There is one strategy from category 1 which is not used is linking to cognates. The reason of students in having vocabulary learning strategies refers to their limitation in vocabulary. It means that the subjects are learning English as a foreign language. So, they were using those strategies in learning English vocabulary.